2017
DOI: 10.1186/s12889-017-4725-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in coverage for measles and varicella vaccination in toddlers – analysis of factors influencing parental acceptance

Abstract: Background: In 2004, routine varicella vaccination was introduced in Germany for children aged 11-14 months. Routine measles vaccination had already been introduced in 1973 for the same age group, but coverage is still too low (<95%) in some areas to eliminate measles. The present study assessed varicella and measles vaccination coverage and determinants of parental acceptance in two study regions, situated in Northern and Southern Bavaria (Germany). Methods: From 2009 to 2011, annual cross-sectional parent su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…We also found consistent results for notification by two or more letters, the proportion of non-Japanese elementary school students, and the moving-in rate. A study in Germany found from annual cross-sectional parent surveys that nursery school attendance was positively associated with vaccination coverage and that caregivers' school education was negatively associated (Hagemann et al 2017). From the perspective of our hypothesis, their findings can be interpreted as follows: attendance at nursery schools might represent information sharing among caregivers and nurse teachers.…”
Section: Specificationmentioning
confidence: 72%
See 1 more Smart Citation
“…We also found consistent results for notification by two or more letters, the proportion of non-Japanese elementary school students, and the moving-in rate. A study in Germany found from annual cross-sectional parent surveys that nursery school attendance was positively associated with vaccination coverage and that caregivers' school education was negatively associated (Hagemann et al 2017). From the perspective of our hypothesis, their findings can be interpreted as follows: attendance at nursery schools might represent information sharing among caregivers and nurse teachers.…”
Section: Specificationmentioning
confidence: 72%
“…To date, many factors associated with vaccination coverage have been discussed in the literature: income (Klevens and Luman 2001;Smith et al 2004;Wu et al 2008;Sakai et al 2015;Hagemann et al 2017), physician density (Smith et al 2011), caregiver education (Wei et al 2009), and a recommendation or reminder from a physician or public health authorities (Anderberg et al 2011;Vannice et al 2011;Stockwell et al 2012;Gargano et al 2013;Busso et al 2015;Sakai. 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As measles is highly infectious, under-immunized communities (also called pockets of susceptibles) resulting from local heterogeneity in vaccine coverage can lead to large, long-lasting outbreaks [30][31][32][33][34]. Detecting these pockets of susceptibles can be challenging, as historical local values of coverage throughout a given country are rarely available.…”
Section: Introductionmentioning
confidence: 99%
“…In Bavaria, the second largest German Federal State, varicella vaccinations and their impact were studied in the frame of the 'Bavarian Varicella-Surveillance Project' [12][13][14][15][16][17][18]. Similarly to other regions in Germany until 2011, the coverage for first-dose varicella vaccination in children aged 18-36 months increased in the two observed Bavarian regions to 69% and 83%, respectively [12][13][14]. Corresponding to the observed increase in coverage, the estimated incidence of pediatric VRH of 13.3 and 16.8 per 100,000 children \ 17 years of age in Bavarian hospitals in 2005 and 2006 continuously decreased in the following years to 4.8 in 2011 [16].…”
Section: Introductionmentioning
confidence: 99%